Advances in the synthesis of β-alanine - Song, Peng; Zhang, Xue; Wang, Shuhua; Xu, Wei; Wei, Feng (Frontiers in Bioengineering and Biotechnology, 2023)
β-Alanine is the only naturally occurring β-type amino acid in nature, and it is also one of the very promising three-carbon platform compounds that can be applied in cosmetics and food additives and as a precursor in the chemical, pharmaceutical and material fields, with very broad market prospects. β-Alanine can be synthesized through chemical and biological methods. The chemical synthesis method is relatively well developed, but the reaction conditions are extreme, requiring high temperature and pressure and strongly acidic and alkaline conditions; moreover, there are many byproducts that require high energy consumption. Biological methods have the advantages of product specificity, mild conditions, and simple processes, making them more promising production methods for β-alanine. This paper provides a systematic review of the chemical and biological synthesis pathways, synthesis mechanisms, key synthetic enzymes and factors influencing β-alanine, with a view to providing a reference for the development of a highly efficient and green production process for β-alanine and its industrialization, as well as providing a basis for further innovations in the synthesis of β-alanine.